Rewrite ... logF=logG+logH−log(1/M)−2*logR ... in the form F=... using laws of logarithms

logF=logG+logH−log(1/M)−2*logR Simplify RHS using law of logarithms, 

logF=log(GH)−log(1/M)−2logR             using law of addition
logF=log(G
HM)−2logR                      using law of subtraction
logF=log((GHM)/R^2))                        using law of powers and subtraction so by taking logs of both sides we have:

F = (GHM) / R^2 

Answered by Ambrose R. Maths tutor

5505 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Solve the following equation: x^(3) - 6x^(2) + 11x - 6 = 0


How to differentiate x^2 + y^2 - 2x + 6y = 5


What is a radian?


If y = (1+3x)^2, what is dy/dx?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences